The association of levels of vitamin D and lipid profiles with calcaneal spur - Ahmed Ibrahim Hammad; Marwa Ahmed Kamel (Egyptian Rheumatology and Rehabilitation)
Abstract Background Calcaneal spurs (CS) are bony growths on the heel bone. While often asymptomatic, they can cause heel pain and impact quality of life. In addition to mechanical stress, recent studies suggest that metabolic factors such as vitamin D deficiency and lipid profile abnormalities play a role in their formation. Objective To investigate the relationship between vitamin D levels, lipid profiles, and calcaneal spurs formation. Results The mean age was 41.7 ± 5.78 years for the case group and 41.73 ± 5.35 years for the control group. The case group had significantly higher mean weight and BMI than the control group, with P values < 0.0001 for both. Additionally, the case group had significantly higher mean levels of triglycerides, LDL, and total cholesterol, with P values of < 0.0001, 0.001, and < 0.0001, respectively. The case group also had significantly lower mean levels of 25-(OH) D and calcium than the control group, with P values < 0.0001 for both. Conclusions and recommendations. This study identifies obesity (BMI) and low calcium as key predictors of calcaneal spur formation, with BMI emerging as the most significant predictor. These findings stress the importance of managing obesity, dyslipidemia, and vitamin D and calcium deficiency to reduce the impact of calcaneal spurs.